Investigative genetic genealogy for unidentified human remains cases in Oregon. (December 2022) - Greytak, Ellen M.; Cady, Janet; Vance, Nici; Moore, CeCe; Armentrout, Steven L.
Abstract: In 2018, the Oregon State Medical Examiner's Office (OSME) received a grant from the Bureau of Justice Assistance to use investigative genetic genealogy (IGG) with Parabon NanoLabs (Parabon) to attempt to make identifications in their unidentified human remains cases. Samples were screened for DNA quantity and quality, and selected samples were sent for genome-wide single nucleotide polymorphism (SNP) generation. This multi-year collaboration has been extraordinarily successful: of 43 cases submitted, 39 cases have been investigated using IGG, and 30 have resulted in an identification so far.